Two histone fold proteins, CHRAC-14 and CHRAC-16, are developmentally regulated subunits of chromatin accessibility complex (CHRAC) - Corona, Davide F.V. (Oxford University Press, 2000)
The ISWI ATPase of Drosophila is a molecular engine that can drive a range of nucleosome remodelling reactions in vitro. ISWI is important for cell viability, developmental gene expression and chromosome structure. It interacts with other proteins to form several distinct nucleosome remodelling machines. The chromatin accessibility complex (CHRAC) is a biochemical entity containing ISWI in association with several other proteins. Here we report on the identification of the two smallest CHRAC subunits, CHRAC-14 and CHRAC-16. They contain histone fold domains most closely related to those found in sequence-specific transcription factors NF-YB and NF-YC, respectively. CHRAC-14 and CHRAC-16 interact directly with each other as well as with ISWI, and are associated with functionally active CHRAC. The developmental expression profiles of both subunits suggest specialized roles in chromatin remodelling reactions in the early embryo for both histone fold subunits.